Preaching the Sacraments: Catechesis for the Laity or Education for the Clergy? - Roger Andersson (Erebea, 2011)
Es un estudio sobre una serie de quince cortos sermones (collationes) acerca de los sacramentos que fueron predicados por un fraile no identificado (‘frater Ingemarus’) en el contexto de las visitas realizadas por su arzobispo Birgerus Gregorii a la diócesis de Uppsala durante el invierno de 1376-77. Tras resumir brevemente el contenido de los sermones, el autor debate la cuestión de su audiencia, argumentando que las “collationes” no iban dirigidas sólo a los sacerdotes, sino también, a lo que parece, a todo el que se hallaba presente en las iglesias visitadas. Su evocadora imaginería sugiere que podían haber sido concebidos específicamente para los laicos, un auditorio necesitado no sólo de instrucción en los siete sacramentos sino también de impulso para beneficiarse de sus efectos. This study investigates into a series of fifteen short sermons (collationes) on the Sacraments, preached by an unidentified friar (‘frater Ingemarus’) in connection with the visitations that his archbishop Birgerus Gregorii made in the diocese of Uppsala in the winter of 1376-77. The contents of the sermons are briefly summarized and the question of audience is discussed. The article argues that the collationes were not only directed to the priests but seemingly to all who were present in the churches visited by the bishop. The evocative imagery suggests that they may have been targeted specifically at lay people, an audience that needed not only instruction about the Seven Sacraments but also needed to be moved in their hearts to fully grasp their effects.